Molecular Dynamics Simulations of Mite Aquaporin DerfAQP1 from the Dust Mite Dermatophagoides farinae (Acariformes: Pyroglyphidae). (24th July 2020) - Wang, Li-lei; Yu, Li-li; Zhou, Ying; Wu, Mei-li; Teng, Fei-xiang; Wang, Nan; Cui, Yu-bao
Abstract : Aquaporins are a large family of transmembrane channel proteins that facilitate the passive but highly selective transport of water and other small solutes across biological membranes. House dust mite ( Dermatophagoides farinae ) is the major source of household immunogens, and we have recently reported six cDNA sequence encoding aquaporins from this mite species. To better understand the structure and role of mite aquaporin, we constructed a tertiary structure for DerfAQP1 by homology modeling from the X-ray structure of malaria aquaporin PfAQP (Protein Data Bank code No. 3C02) and conducted molecular dynamics simulation. The simulation arranged seven water molecules in a single file through the pores of the DerfAQP1. Further, two conserved Asn-Pro-Ala motifs were located on Asn203 and Asn77; residues Arg206, Trp57, Met190, Gly200, and Asp207 constituted an extracellular vestibule of the pore; and residues His75, Val80, Ile65, and Ile182 constituted the cytoplasmic portions. The overall free energy profile for water transport through DerfAQP1 revealed an energy barrier of ~2.5 kcal/mol. These results contribute to the understanding of mite physiology and pathology.